Overview of the key technology of photonic firewall at high speed - Shanguo HUANG; Xin LI; Ying TANG; Junfeng GUO (Tongxin xuebao)
In order to maintain the security of optical network,it is urgent to research and deploy photonic firewall which can effectively process high-speed optical signals to replace existing electronic firewall which consumes high energy.After a brief review of the principle of photonic firewall,the pattern matching technology based on correlation operation and all-optical logic gates were summarized,and the matching systems was compared according to their advantages and disadvantages.Besides,the realization methods of all-optical logic gates were introduced.Finally,the next research direction and development trend of all-optical pattern matching were prospected:more efficient system structure or non-linear devices with faster response speed.The survey shows that photonic firewall based on all-optical pattern matching has a good application prospect in network security.